2017
DOI: 10.1002/chem.201702884
|View full text |Cite
|
Sign up to set email alerts
|

Polyaspartates as Thermoresponsive Enantiodifferentiating Helically Chiral Alignment Media for Anisotropic NMR Spectroscopy

Abstract: Lyotropic liquid crystalline phases of poly-β-phenethylaspartates are presented as new helically chiral enantiodifferentiating alignment media with thermoresponsive properties. In addition to displaying the highest enantiodifferentiation observed for homopolypeptides, the alignment media undergo a temperature induced helix reversal without perturbing the nematic phase. This offers the opportunity to measure residual dipolar couplings (RDCs) in high and low temperature helix conformation (P- and M-helix) in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 45 publications
0
39
0
1
Order By: Relevance
“…Here it should be noted that the helix conformation changes from, for example, P‐ to M‐ helix, but the amino acid configuration remains the same. In our previous paper we demonstrated that polyaspartates before and after helix reversal are diastereomeric alignment media, thus furnishing β ‐angles very different from zero. For the copos this becomes quite evident when comparing RDCs obtained at 300 K with RDCs obtained at 312 K (Figure ).…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Here it should be noted that the helix conformation changes from, for example, P‐ to M‐ helix, but the amino acid configuration remains the same. In our previous paper we demonstrated that polyaspartates before and after helix reversal are diastereomeric alignment media, thus furnishing β ‐angles very different from zero. For the copos this becomes quite evident when comparing RDCs obtained at 300 K with RDCs obtained at 312 K (Figure ).…”
Section: Figurementioning
confidence: 96%
“…Recently, we started to investigate LLC phases of high molecular weight poly‐β‐phenethylaspartates (PPA) as new helically chiral alignment media . In addition to displaying enantiodifferentiating abilities, they possess the intrinsic property to undergo a temperature induced helix reversal without perturbing the nematic phase .…”
Section: Figurementioning
confidence: 99%
“…To evaluate these, we performed a series of experiments with both enantiomers of isopinocampheol [(+)‐ and (−)‐IPC]. We chose IPC as an analyte because both enantiomers are commercially available and it has proven as a reliable test substance for new alignment media . We prepared the anisotropic samples above the critical concentration and verified the stability of the LLC‐phase by 2 H NMR spectra until no line shape change occurred.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to invert the helix sense in the backbone of the polymer at a certain temperature changes the orientation of the analyte. Therefore, two sets of RDCs as a result of two independent orientations in one sample are obtained …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Schwab et al . achieved extraordinarily high enantiodifferentiation ( β values of up to 80°) in poly‐ β ‐phenetyl‐ L ‐aspartate (PPLA) and a copolymer made of PPLA and poly‐ β ‐benzyl‐ L ‐aspartate (PBLA) . From the thermoresponsive behavior of the aspartates, they could show that the enantiodifferentiation is imposed by both the helicity of the alignment medium and the chirality of the amino acid.…”
Section: Introductionmentioning
confidence: 99%